Potential of spore-forming bacteria as biocontrol agents of wheat foliar diseases under laboratory and greenhouse conditions - Alippi, Adriana Mónica (2000)
The potential of Bacillus subtilis, Bacillus cereus, Bacillus licheniformis, Bacillus pumilus, Brevibacillus laterosporus and Paenibacillus polymyxa as biocontrol agents of four foliar necrotrophic pathogens of wheat in Argentina has been evaluated. The following assays were used: (a) effect of the bacterial antagonists on fungal growth in the central disk test with paired cultures, (b) effect of the antagonists on the germination of fungal spores in the paired suspension assay, and (c) reduction of disease severity in greenhouse experiments. The observed effects were specific for the antagonist-pathogen combination investigated. In the paired culture test, most of the bacterial antagonists inhibited the mycelial growth of the four pathogens tested at 14 days of the evaluation. B. licheniformis showed the best results for controlling Septoria tritici and Drechslera tritici-repentis whereas it was the worst against Bipolaris sorokiniana. In the case of Alternaria triticimaculans, the best were B. laterosporus, P. polymyxa and B. licheniformis. Microscopic examination of excised pieces of the fungal colony perimeters showed clear differences among treatments and controls in hyphal morphology (plasmolysis and vacuolation of hyphae, irregular texture in the cytoplasm, formation of chlamydospores). In the central disk test, mycelial necrosis of A. triticimaculans was induced by B. laterosporus, P. polymyxa and B. pumilus. Similar results were obtained with B. sorokiniana in the presence of B. licheniformis and B. subtilis and D. tritici-repentis with B. pumilus. In some combinations, the presence of inhibition haloes or bacterial chemotaxis were observed. In the paired suspension assay, all the bacteria except B. cereus, inhibited the conidial germination of S. tritici. Only P. polymyxa, B. licheniformis and B. laterosporus inhibited the conidial germination of A. triticimaculans, B. laterosporus being the most effective. Although all the bacteria inhibited the conidial germination of B. sorokiniana, the most efficient were B. licheniformis, B. cereus and B. laterosporus. In greenhouse experiments, P. polymyxa and B. cereus were the most efficient to reduce disease severities produced by S. tritici and A. triticimaculans; on the contrary, these bacteria were not effective against B. sorokiniana and D. tritici-repentis. B. laterosporus BLA 170 showed a good behaviour against all the fungal pathogens, particularly for D. tritici-repentis and B. sorokiniana. This is the first report on the efficacy of B. laterosporus against fungal wheat pathogens.